Substantiation of the approximation methods of the information loss channels models - Конахович, Г. Ф.; Андрухович, П. О. (Problems of Informatization and Control, 2009)
Several methods of approximation of the findings that were achieved during the conduction of the experiment are analyzed, the main concepts of those approximations are given. The supplemented method of spline-approximation is proposed. Calculative conclusions are done regarding the choice of the approximation method with the least mistake